Measuring what matters: developing indicators for online content evaluation competencies in elementary school - Jocham, Tina; Pohlmann-Rother, Sanna (Frontiers in Education, 2025)
IntroductionChildren increasingly engage with online content from an early age, but often lack the competencies to critically evaluate it. To foster these skills, suitable assessment instruments are required, yet none currently exist for the elementary school level. Drawing on a conceptual framework comprising four evaluation criteria applied across five content areas, this study addresses the need for a target group-specific operationalization. The aim was to derive concrete indicators to guide the development of an assessment instrument designed to measure elementary school children’s ability to evaluate online content.MethodsTo specify evaluation criteria within the content areas, a qualitative preliminary study was conducted. All German curricula were systematically examined with respect to evaluation competencies in digital contexts. In addition, interviews with media experts were carried out. Both the curricula and the interviews were analyzed using qualitative content analysis to refine and extend existing research with indicators tailored to elementary school children.ResultsIndicators were derived for four evaluation criteria across various forms of online content relevant to elementary school children. For design aspects, indicators include, for example, understanding the role of likes and comments in personalized content or interpreting emojis in chat messages. Indicators for credibility involve distinguishing facts from opinions and evaluating the intent behind influencer content or chain messages. Regarding closeness to reality, children are expected to differentiate real from fictional content, such as assessing YouTube pranks. Finally, identification relates to recognizing digital phenomena, for instance, distinguishing between educational videos and hidden advertising.DiscussionThis study highlights the development of indicators for assessing elementary school children’s evaluation of online content. These indicators enable the construction of standardized items that capture both knowledge and procedural skills using age-appropriate, multimodal online materials.